Collective bargaining, discrimination, social security and European integration : papers & proceedings of the VIIth European Regional Congress of the International Society for Labour Law and Social Security Law, Stockholm, September 2002 /: papers & proceedings of the VIIth European Regional Congress of the International Society for Labour Law and Social Security Law, Stockholm, September 2002. (2003) - Unknown
No abstract available